'Sometimes people kill you emotionally': policing inclusion, experiences of self-identified homosexual youth in secondary schools in Namibia. Issue 3 (3rd July 2017) - Brown, A.
Abstract: This article reports on the exclusionary experiences of self-identified homosexual learners in mainstream schools in Namibia. Namibia adopted the UNESCO's Salamanca Statement on Inclusive Education in 1994 which promulgates that schooling should cater for all children regardless of their differences. However, Namibia still upholds legislation that deems homosexuality as a criminal offence which subsequently presents numerous challenges on how school youth with same-sex identities are framed and treated. Focus group discussions with 12 self-identified homosexual learners in secondary schools in Windhoek, Namibia were conducted as part of a larger national and regional study. The study found that participants were subjected to homophobic violence by school management, teachers and learners which were fuelled by the homosexual dissonance and silence in the country. Violence ranged from physical beatings, stabbing, stone throwing and name calling to denial of educational access. Although the Policy on Inclusive Education paves way for all children to participate fully in the education system, it is evident that all learners are not equally valued, protected and supported. This paper advocates for the revisit of Namibia's legislation that does not endorse human rights of sexual diverse citizens and serve as a justification as a justification tool towards discrimination.